Comparative proteomic analysis of hen egg yolk plasma proteins during embryonic development. Issue 12 (10th September 2019) - Meng, Yaqi; Sun, Haohao; Qiu, Ning; Geng, Fang; Zhu, Fangli; Li, Shugang; Huo, Yinqiang
Abstract: Avian egg yolk provides essential nutrients and physiological support for the developing embryo. To reveal the dynamics of yolk proteins during the entire period of incubation, we analyzed the alterations of egg yolk plasma proteins at different times during incubation (day 0, 7, 14, and 18). Day 14 (D14) of incubation was considered as the key point on the alteration of egg yolk proteins according to the SDS‐PAGE analysis. The two‐dimensional electrophoresis‐based comparative proteomic analysis was conducted, and 26 spots representing 13 proteins were detected with significant changes in abundance. An accelerating transfer of ovalbumin from egg white into egg yolk was observed at D14 in fertilized eggs but not detected in unfertilized eggs, indicating an unrevealed absorbing pathway for the egg proteins/peptides particularly in fertilized eggs. Meanwhile, the abundance of yolk riboflavin‐binding protein constantly decreased after D14, which might meet the need for essential riboflavin during embryo development. Practical applications: These findings provide fundamental insight into the effects of incubation on egg yolk plasma protein alterations during the entire embryonic development for a better understanding of plasma protein biological functions, especially in nutrient transportations and the formation of embryonic organs. Abstract : In conclusion, twenty‐six protein spots representing 13 proteins in yolk plasma were identified with significant changes in abundance. Day 14 (D14) of incubation was considered as the key point on the alteration of egg yolk proteins. This study at least gave a global view of egg yolk plasma protein alterations during the entire incubation period and provided a novel insight for revealing biological functions of egg proteins for embryogenesis.